2002
DOI: 10.1007/s00467-001-0816-8
|View full text |Cite
|
Sign up to set email alerts
|

Nephrocalcinosis in preterm infants: a single center experience

Abstract: The risk of nephrocalcinosis in preterm infants is considerable, but conflicting numbers are given for the actual incidence (10-65%). Furosemide induced hypercalciuria is said to be the main risk factor. We examined retrospectively the incidence, causes and outcome of nephrocalcinosis in preterm infants born in our hospital from 1988 to 1998 ( n=2190). An abnormal renal echogenicity or nephrocalcinosis was seen in 31 infants (29.7+/-3.3 weeks gestational age; 1307+/-690 g birth weight). Nephrocalcinosis was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
1
14

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 33 publications
4
51
1
14
Order By: Relevance
“…This is in contrast with results of a study by Saarela et al, who found no significant difference in GFR at a mean age of 4.7 years between 20 former preterms with and 20 without NC in the neonatal period [73]. Hoppe et al and Porter et al also observed normal GFR after 3-6 years and 5.8-7.7 years, respectively, in 12 and 14 prematurely born children with NC [14,74].…”
Section: Glomerular Functioncontrasting
confidence: 61%
See 4 more Smart Citations
“…This is in contrast with results of a study by Saarela et al, who found no significant difference in GFR at a mean age of 4.7 years between 20 former preterms with and 20 without NC in the neonatal period [73]. Hoppe et al and Porter et al also observed normal GFR after 3-6 years and 5.8-7.7 years, respectively, in 12 and 14 prematurely born children with NC [14,74].…”
Section: Glomerular Functioncontrasting
confidence: 61%
“…However, persistence for several years has been described [11,14,69,[71][72][73][74]. In the largest ongoing study of preterm neonates, NC persisted in 34%, 15% and 10% after 15 months, 30 months and 7.4 (±1.0) years, respectively (Fig.…”
Section: Persistence Of Nephrocalcinosismentioning
confidence: 96%
See 3 more Smart Citations